2008
DOI: 10.2166/wst.2008.274
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on suspended solids sources in urban stormwater runoff using 7Be and 210 Pb as tracers

Abstract: Pb ratio decrease suggests that 60^12% of suspended solids at sewer outlet originated from the drainage system sediments, the rest was from the wash-off of urban ground dust during the rainfall events. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Compared to agricultural and forested landscapes, relatively few studies have quantitatively determined the sources of sediment in urban waterheds with studies to date being concentrated in Australia (e.g., Ormerod, 1999;Charlesworth et al, 2000), Brazil (e.g., Poleto et al, 2009;Franz et al, 2014), China (e.g., Yin and Li, 2008), UK (e.g., Charlesworth et al, 2000;Carter et al, 2003) and USA (e.g., Devereux et al, 2010). In part this stems from the inherent hydrological complexities associated with urban areas, alongside multiple diffuse sediment sources, and the potential for transformations in the physical and chemical properties of the sediment (Taylor and Owens, 2009).…”
Section: Urban Landscapesmentioning
confidence: 99%
“…Compared to agricultural and forested landscapes, relatively few studies have quantitatively determined the sources of sediment in urban waterheds with studies to date being concentrated in Australia (e.g., Ormerod, 1999;Charlesworth et al, 2000), Brazil (e.g., Poleto et al, 2009;Franz et al, 2014), China (e.g., Yin and Li, 2008), UK (e.g., Charlesworth et al, 2000;Carter et al, 2003) and USA (e.g., Devereux et al, 2010). In part this stems from the inherent hydrological complexities associated with urban areas, alongside multiple diffuse sediment sources, and the potential for transformations in the physical and chemical properties of the sediment (Taylor and Owens, 2009).…”
Section: Urban Landscapesmentioning
confidence: 99%
“…The high contribution of urban sources (up to 40% sewage and RDS) illustrates the marked contrast of urban sediments to those in non-urbanised river basins. Yin and Li (2008) used a similar approach using 7 Be and 210 Pb as tracers to estimate that about 60% of the suspended sediments at the outlet of a sewer system in Wuhan City, China was derived from the drainage system (gutter sediments and combined sewer sediments), with about 40% from RDS. These findings are in general agreement with Nelson and Booth (2002) who found that, as well as landslides and channel bank erosion, 15% of sediment in an urbanised catchment was from road surface erosion.…”
Section: Sources Of Sediment and Contaminants To Urban Riversmentioning
confidence: 99%
“…Urban systems may exhibit a 'first-flush' or 'initial micro-pulse' (Lee et al 2002;Lawler et al 2006;Yin and Li 2008) whereby there is an initial increase in the sediment flux (concentration and/or load) due to a coupling between urban sources (i.e. RDS, CSO delivery) and the urban river network by rain events.…”
Section: Sediment and Contaminant Concentrations And Fluxesmentioning
confidence: 99%
“…Lee and Heaney [19] about 52 years of long-term rainfall data to demonstrate that imperviousness of the surface is an important indicator of the impact of urbanization on stormwater systems and has a direct influence on stormwater quality and quantity. Identification of SS sources in urban stormwater runoff using radioactive tracers ( 7 Be and 210 Pb) was done by Yin and Li [20]. They found that 60±12% of SS at the sewer outlet originated from the drainage system sediments while the rest was from the wash-off of urban ground dust during the rainfall events.…”
Section: Sediment Load and Suspended Solid Concentrationmentioning
confidence: 99%